2014
DOI: 10.1017/s104161021400132x
|View full text |Cite
|
Sign up to set email alerts
|

How are decisions on care services for people with dementia made and experienced? A systematic review and qualitative synthesis of recent empirical findings

Abstract: phone: + 46 (0)13-28 28 94 1. The authors have not entered into an agreement with the funding organization that has limited their ability to complete the research as planned and publish the results.2. The authors have had full control of all the primary data.3. The authors are willing to allow the journal to review their data if requested. 2 ABSTRACTBackground: During recent decades, there has been a growing recognition that people cannot

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…Some ways to handle the process of assessing needs and decide on social care services that are legal in other countries may not be legal in Sweden. In a systematic review of research on how decisions on care services for persons with dementia are made and experienced by those involved (Taghizadeh Larsson & Österholm, 2014), only one study was found with a broader focus on the needs assessment process and the performance of care managers (McDonald, 2010). The study was based on document reviews, reading of case files, and semi-structured interviews with care managers, with the aim of studying the impact of the Mental Capacity Act (MCA) in England and Wales on social workers' approaches to decision making in circumstances of risk.…”
Section: Decision-making Dementia and Social Care Servicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Some ways to handle the process of assessing needs and decide on social care services that are legal in other countries may not be legal in Sweden. In a systematic review of research on how decisions on care services for persons with dementia are made and experienced by those involved (Taghizadeh Larsson & Österholm, 2014), only one study was found with a broader focus on the needs assessment process and the performance of care managers (McDonald, 2010). The study was based on document reviews, reading of case files, and semi-structured interviews with care managers, with the aim of studying the impact of the Mental Capacity Act (MCA) in England and Wales on social workers' approaches to decision making in circumstances of risk.…”
Section: Decision-making Dementia and Social Care Servicesmentioning
confidence: 99%
“…Persons with dementia might also be deceived into becoming users of social care services (Elliott, Gessert & PedenMcAlpine, 2009;Forbes et al, 2012;Golden, 2010;Weber & Bailey, 2005). For example they might be told by their relatives that they are going to a hotel when they in fact are being moved to a residential care facility or being told that they are going to work when they are going to attend a day care center (Taghizadeh Larsson & Österholm, 2014). There are also instances when relatives inform the person with dementia that they are being relocated to a residential care facility and push through their decision even though the person with dementia objects (Chang, Schneider & Sessanna, 2011;Chene, 2006;Livingston et al, 2010).…”
Section: Decision-making Dementia and Social Care Servicesmentioning
confidence: 99%
See 3 more Smart Citations